EFISENSI BELANJA OPERASIONAL KEMENTERIAN/LEMBAGA - Nurrochmah Adha Kusumawati; Andrie Mulya Febrianto; Mahfudin Mahfudin; Niken Ajeng Lestari (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2018)
This study aims to analyze the causes of high and varied operationalspending’s valuesat the ministry/institution ​​by first comparing the concept of operational spending inRKA K / L with concepts according to academic theory. Then, an alternative concept of operational spending is prepared in accordance with the theory. By using data exercise, it was found that alternative conceptoperational expenditure that fit the theory resulted in lower and more efficient operational spending’s values. In addition, unit clustering was carried out to obtain a more standardized operational spending’s value.